The Part of Animals Bunches in Progressing the Status of Social Agriculturists within the Semangga Merauke Area - Abdul Rizal; Adrianus Adrianus; Semuel Batlajery; Simon Siamsa; Apolinaris S.A; Romualdus T.P.M.D; Adrian Tawai; Rina Astarika (Pascasarjana Universitas Sulawesi Tenggara, 2023)
This study aims to determine (1) the role of livestock groups in increasing the social status of breeders, (2) to determine the social status of breeders (3) to determine the relationship between the role of livestock groups in increasing the social status of farmers. This research was conducted in Semangga District from June 2022 until completion. The population sampled in this study were breeders living in the Semangga District, namely, 30 respondents. The analytical tool used is sperm rank analysis. The variables observed in this study were livestock groups and the social status of breeders. The results showed that: (1) The role of livestock herds in increasing the social status of farmers was in a good category, (2) the social status of breeders in Semangga District was in the moderate category, (3) the role of livestock herds was positively related to increasing the social status of farmers in Semangga District